Adherence to the Mediterranean diet and colorectal cancer risk: a large case control study in the Moroccan population - Khaoula El Kinany; Zineb Hatime; Achraf El Asri; Abdelilah Benslimane; Meimouna Deoula; Btissame Zarrouq; Pagona Lagiou; Karima El Rhazi (Public Health Nutrition)
Abstract